Quality of Life and Related Dimensions in Cancer Patients Treated with Mistletoe Extract (Iscador): A Meta-Analysis. (14th June 2011) - Büssing, Arndt; Raak, Christa; Ostermann, Thomas
Abstract : Objectives . The aim of this meta-analysis was to determine the effectiveness of the fermented plant extract Iscador, produced from the white-berry European mistletoe, in the treatment of patients with cancer with respect to quality-of-life- (QoL-) associated measures. Methods . We searched databases such as PubMed/Medline, Excerpta Medica Database (EMBASE), CAMbase, and other for controlled clinical studies on parameters associated with QoL. Outcome data were extracted and converted into standardized mean differences and their standard errors. Results . Thirteen prospective and controlled studies which met the inclusion/exclusion criteria reported positive effects in favor of the Iscador application. A random-effect meta-analysis estimated the overall treatment effect at standardized mean difference = 0.56 (CI: 0.41 to 0.71, P < .0001 ). However, the methodological quality of the studies was poor. Conclusions . The analyzed studies give some evidence that Iscador treatment might have beneficial short-time effects on QoL-associated dimensions and psychosomatic self-regulation.